Optimal SoC range determination for battery storage to smooth wind power output and extend battery lifespan - Mehran Alitabar; Mohsen Sedighi; Seyed Mehdi Abedi Pahnehkolaei; Alireza Ghafouri (PLoS ONE, 2025)
The increase in the consumption of electrical energy in the world has increased the trend towards renewable energy for the production of electricity in small and large scales. One of the major renewable energies that have attracted the attention of experts are wind turbine (WT) resources. Due to their dependence on wind speed, these sources have large fluctuations in output power. For this purpose, it is necessary to use electrical energy storage devices that can reduce the fluctuations of wind turbine output power by proper and fast charging and discharging. The use of such energy storage systems also increases network costs and operational complexity. Also, considering that wind turbine output power fluctuations are high and at a high speed, the charging and discharging of these energy storage devices will also occur with a large number of times and will lead to a reduction in the life of this equipment. If the size of these batteries is chosen in such a way that they can be charged and discharged in smaller intervals, their lifespan will be improved and the use of these equipment will be in more favorable conditions. In this paper, an attempt will be made to choose the appropriate state of charge (SoC) range for energy storage devices along with wind turbine resources. The simulation of wind turbine and battery storage in micro-grid and in on-grid condition has been implemented in MATLAB software.